Customer engagement di social media marketing: Anteseden dan konsekuensinya pada brand loyalty - Nurfarida, Iva Nurdiana; Sarwoko, Endi; Rusno, Rusno (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2024)
There have been many studies on social media marketing, but researchers still ignore the role of social media on customer engagement initiatives as well as on brand loyalty. The study aims to investigate the influence of social media marketing on brand loyalty through customer engagement. The study was conducted on customers of culinary centers in Malang City, the sample was selected purposively involving 120 respondent. Data were collected using questionnaires distributed online and analyzed using PLS-SEM. The research findings revealed that social media marketing is able to increase brand loyalty; in addition, this influence is also mediated by customer engagement. Social media marketing is able to increase customer engagement, which will also have an impact on brand loyalty. Further researchers could examine differences in customer engagement across social media marketing channels.